Funnel‐freezing versus heat‐stabilization for the visualization of metabolites by mass spectrometry imaging in a mouse stroke model. Issue 11 (9th May 2016) - Mulder, Inge A.; Esteve, Clara; Wermer, Marieke J.H.; Hoehn, Mathias; Tolner, Else A.; van den Maagdenberg, Arn M.J.M.; McDonnell, Liam A.
Abstract : Tissue preparation is the key to a successful matrix‐assisted laser desorption/ionization (MALDI) mass spectrometry imaging (MSI) experiment. Rapid post‐mortem changes contribute a significant challenge to the use of MSI approaches for the analysis of peptides and metabolites. In this technical note we aimed to compare the tissue fixation method ex‐vivo heat‐stabilization with in‐situ funnel‐freezing in a middle cerebral artery occlusion (MCAo) mouse model of stroke, which causes profound alterations in metabolite concentrations. The influence of the duration of the thaw‐mounting of the tissue sections on metabolite stability was also determined. We demonstrate improved stability and biomolecule visualization when funnel‐freezing was used to sacrifice the mouse compared with heat‐stabilization. Results were further improved when funnel‐freezing was combined with fast thaw‐mounting of the brain sections.